Carbon fiber‐reinforced epoxy composite properties improvement by incorporation of polydopamine sizing at fiber–matrix interface. Issue 4 (27th January 2023) - Qin, Wenzhen; Lei, Kaixuan; Yan, Meiling; Li, Zhongkai; Yan, Yi; Hu, Yongwei; Wu, Zhijun; He, Jianwei; Chen, Liang
Abstract: To gain better interfacial and mechanical performances of carbon fiber‐reinforced epoxy resin (CF/EP) composites, the surface modification of CF was carried out via a simple mild method. The polydopamine (PDA) was applied to size the CF, as well as the influence of PDA sizing time on CF was elucidated. As the PDA‐deposited time increases, a growing number of PDA nanoparticles were adhered on CF surface, associating with appearance of PDA agglomerates. Through analyzing the results, the optimum PDA sized time was 24 h. The introduction of PDA increases the chemical reaction and mechanical interlocking between fiber and matrix. Compared with unsized CF, the tensile strength of PDA 24 h sized CF was improved by 27.0%, the interlaminar shear strength, flexural and impact strength of PDA 24 h sized CF/EP composites increased by 103.7%, 65.6%, and 163.6%, respectively. Furthermore, the fracture topographies of CF/EP composite strikingly implied that the PDA has a positive impact on the mechanical performances of CF/EP composites. Abstract : 1. Interface properties of CFRP improvement by incorporation of polydopamine (PDA) at T300. 2. As the PDA‐deposited time increases, the interlaminar shear strength, flexural and impact strength increased.